2022
DOI: 10.3390/antiox11020400
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Model-Based Assessment of Indoxyl Sulfate-Induced Oxidative Stress and Its Impact on Renal and Cardiac Development

Abstract: Kidney disease patients may have concurrent chronic kidney disease-associated mineral bone disorder and hypertension. Cardiovascular disease (CVD) and neuropathy occur due to kidney failure-induced accumulation of uremic toxins in the body. Indoxyl sulfate (IS), a product of indole metabolism in the liver, is produced from tryptophan by the intestinal flora and is ultimately excreted through the kidneys. Hemodialysis helps renal failure patients eliminate many nephrotoxins, except for IS, which leads to a poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Additionally, Tang PW et al investigated the impact of IS on the development of zebrafish embryos, especially on cardiac and renal development [ 220 ]. At 24 hpf, zebrafish were exposed to IS at concentrations ranging from 2.5 to 10 mM.…”
Section: Zebrafish As a Model To Study Uremic Cardiotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Tang PW et al investigated the impact of IS on the development of zebrafish embryos, especially on cardiac and renal development [ 220 ]. At 24 hpf, zebrafish were exposed to IS at concentrations ranging from 2.5 to 10 mM.…”
Section: Zebrafish As a Model To Study Uremic Cardiotoxicitymentioning
confidence: 99%
“…To evaluate the impact of IS on renal function, the embryos were soaked with 2.5 mM of IS at 24 hpf and injected with 50 ng of 10 kDa dextran conjugated with Rhodamine fluorescent dye into the cardiac venous sinus at 48 hpf, showing abnormal renal development after the exposure to 1.25 mM and 2.5 mM of IS. To investigate the molecular pathway involved in this alteration, the authors demonstrated that IS affected zebrafish development via the ROS and MAPK pathways, which subsequently led to inflammation in the embryos [ 220 ].…”
Section: Zebrafish As a Model To Study Uremic Cardiotoxicitymentioning
confidence: 99%
“…Extreme levels of IS cause endothelial dysfunction and renal injury [14,15]. The metabolomics analysis of the IS effect revealed that it causes CKD in zebrafish via elevation of IS in plasma [16] and in mice [17]. The natural accumulation of IS is known as an indicator of the progression of CKD [8].…”
Section: Introductionmentioning
confidence: 99%
“…The renal dialysis process has also failed to manage the IS-associated CKD improvement due to the binding nature of IS to albumin [20]. Furthermore, numerous studies on IS-associated CKD were investigated with an evaluation of metabolomics and genomic analysis [16,21]. Furthermore, multiple newer molecular pathways and pathological concepts remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, zebrafish has been employed as a non-mammalian model in revealing toxic mechanisms of chemicals and predicting environmental hazards [ 32 , 33 ]. Small body size, short reproductive cycle, high fecundity, and easy husbandry are among the reasons zebrafish became a popular laboratory animal for ecotoxicological studies [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%